Excel maths early skills book 8: add and take away to 20 - Dunbar, Bev (Oxford University Press Karachi, 2006)
"Excel Maths Early Skills: Add and Take Away to 20" introduces young learners to basic addition and subtraction concepts through engaging activities and exercises. The book focuses on building confidence and fluency in numbers up to 20, making math fun and accessible.